Answer:
-2n²
Step-by-step explanation:
Using the image attached:
We see that the second differences (blue ones) are all equal so we conclude that this is a quadratic sequence.
The quadratic sequence has the form:
To find the value of a we just divide second difference ( -4 ) by 2:
Now we have:
Substitute and into the equation above:
Since = -2 and = -8 , after simplification we have:
The solution of this system is:
The general term is :
Answer:
9x^2+22x-2
Step-by-step explanation:
f(g(x))=(3x+1)^2+2(3x+1)-4
=9x^2+16x+6x+2-4
=9x^2+22x-2
to find the soultion of mentioned question you have to put the value of g(x) into f(x) and then solve it like normal ...
Answer:
39cm
Step-by-step explanation: 19cm+15cm+5cm=39
Answer: 30 degrees
Step-by-step explanation:
well 60 divided by 2